2008
DOI: 10.1111/j.1440-1746.2007.05269.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic models in cirrhotics admitted to intensive care units better predict outcome when assessed at 48 h after admission

Abstract: In cirrhotics, prognostic scores in the ICU at 48 h had better discrimination than baseline scores for short-term mortality. SOFA and FOS models had the best performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
2
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 16 publications
(29 reference statements)
1
65
2
5
Order By: Relevance
“…These results are somewhat unsurprising if we bear in mind that the prognosis of acutely ill patients with cirrhosis is influenced not only by the severity of hepatic insufficiency but mainly by the dysfunction of other organ systems and that cirrhotics admitted to ICUs often have extrahepatic organ dysfunction and die of multiple organ failure (12)(13)(14)(34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 86%
“…These results are somewhat unsurprising if we bear in mind that the prognosis of acutely ill patients with cirrhosis is influenced not only by the severity of hepatic insufficiency but mainly by the dysfunction of other organ systems and that cirrhotics admitted to ICUs often have extrahepatic organ dysfunction and die of multiple organ failure (12)(13)(14)(34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 86%
“…In addition, for the first time, we found that SOFA score at 48 hours postadmission is superior to SOFA score at admission in patients with acute complications of cirrhosis. 6 Dhiman et al 1 recognized that important survival factors, such as lactate, pH, phosphates, and ␣-fetoprotein, were not assessed in their study, as the data was collected retrospectively over almost 10 years. Currently, serum lactate is considered an established early prognostic marker of survival in patients with FHF.…”
mentioning
confidence: 99%
“…5 Interestingly, in the latter group of patients, lactate at 48 hours postadmission seems to have a greater impact on survival, compared to lactate at admission. 6 In the setting of FHF, evaluation of lactate at different time points seems to allow more precise assessment of prognosis. For example, similar to Macquillan et al, 7 we found that lactate at 12 hours postadmission had better prognostic accuracy, compared to lactate at admission in acetaminophen-induced FHF.…”
mentioning
confidence: 99%
“…Özellikle erken postoperatif dönemde trombositlerin trombotik komplikasyonlarda önemli rol oynadığını düşünen bazı araştırmacılar trombosit sayısı <20x10 9 /L inmeden veya aktif kanama/sızıntı (diğer faktörler normal olmasına rağmen) olmadan TS transfüzyonu yapılmamasını önermişlerdir. Karaciğer biyopsisi, reoperasyon gibi invaziv girişimler öncesi trombosit sayısı >50x10 9 …”
Section: Postoperatif Kanama Koagülasyon Dengesi Ve Transfüzyon Tedaunclassified
“…Alıcının preoperatif durumu, intraoperatif cerrahi seyir, greft karaciğerin kalitesi, postoperatif enfeksiyon gelişmesi, immünosupresif ilaçların yan etkileri sonucu belirleyen önemli faktörlerdir. Alıcının preoperatif durumunun ciddiyeti ile sağkalım ters orantılı olmakla birlikte bu durum tek belirleyici olmadığından MELD (Model for End-Stage Liver Disease) ve APACHE (Acute Physiology and Chronic Health Evaluation) skorları yüksek olan kritik hastalarda bile KT başarılı olabilmektedir (9,10). Donör yaşı ve preoperatif MELD skoru baz alınarak geliştirilen D-MELD modelinde, skoru yüksek olanlarda (D-MELD>1600) kısa ve uzun dönemde anlamlı olarak daha kötü greft ömrü saptanmıştır (11).…”
Section: Introductionunclassified